Fresh Produce Handling, Sanitation, and Safety Measures: Strawberry, Raspberry, Blackberry, and Blueberry - M. Mahovic; Jeffrey K. Brecht; Steven A. Sargent; Mark A. Ritenour; Keith R. Schneider; Amy Simonne; Jerry Bartz (EDIS, 2003)
This document is FSHN0212, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: October 2002.